E0273 Relationship of peripheral arterial disease, chronic kidney disease, and mortality in Chinese hypertensive patients. (17th November 2010) - Jun, Li; Yingyi, Luo; Xiankai, Li; Yongxia, Qiao; Liqiang, Qin; Dayi, Hu; Jue, Li
Abstract : This study aimed to investigate the associations of chronic kidney disease (CKD), Peripheral arterial disease (PAD) and their combined effect with all-cause and Cardiovascular disease (CVD) mortality in Chinese hypertensive patients. Chinese ankle brachial index (ABI) cohort study including 2992 hypertensive patients aged 35 years or older were enrolled in 2004 and implemented the follow-up visit in 2007. 2505 participants completed baseline and follow-up data. Glomerular filtration rate (GFR) was estimated using the Modification of Diet in Renal Disease equation. ABI was calculated at baseline by measuring systolic pressures on bilateral brachial and tibial arteries. Mortality surveillance was completed from December 2007 to February 2008. Survival analysis was used to compare survival rate in different CKD/PAD groups. The RR of death from all-cause and CVD were adjusted for potential confounders using a Cox regression model. The prevalence of PAD in hypertensive patients with and without CKD was 43.1% and 22.8%, with significant difference between them (p<0.001). For CKD and PAD group, PAD alone group, CKD alone group and neither CKD nor PAD group, the all-cause mortality was 38.6%, 19.6%, 17.3%, 10.5%, and CVD mortality was 23.3%, 13.7%, 11.5%, 5.4%, respectively, with significant differences among each other (p<0.001). The survival rate was significantly lower in CKD and PAD group than in other three groups, for both all-cause and CVD mortality (log-rank: p<0.001). The patients in CKD and PAD group, PAD alone group and CKD alone group had the adjusted RRs of 2.966 (95% CI 2.220 to 3.964), 1.523 (95% CI 1.151 to 2.016) and 1.484 (95% CI 1.067 to 2.063) for all-cause mortality and 3.402 (95% CI 2.343 to 4.939), 2.024 (95% CI 1.434 to 2.856), 1.843 (95% CI 1.225 to 2.773) for CVD mortality, with no CKD or PAD group as the reference. Our study indicated that CKD is a risk factor for PAD. The hypertensive patients combined CKD and PAD had the highest risk for all-cause and CVD mortality. We suggest CKD patients should take ABI measurement for PAD early diagnosis and treatment, and GFR should be used to estimate renal function for PAD patients.